Dinamika Hukum Isbat Cerai Tinjauan Filosofis Terhadap Asas Sederhana Cepat Dan Biaya Ringan - Sobirin, Lisda Apriliani; Napiah, Ilman; Taufik, Taufik; Firdaus, Muhamad Iqbal Ansori (Lex Stricta : Jurnal Ilmu Hukum, 2026)
This study examines the legal dynamics of isbat cerai (validation of unregistered divorce) through a philosophical review of the simple, fast, and low cost (SCBR) principle within Indonesia’s Religious Courts. The high prevalence of unregistered divorces creates an urgent need for retroactive recognition; however, the implementation of isbat cerai remains constrained by regulatory fragmentation, rigid evidentiary standards, and judicial interpretations that tend to be formalistic. Constitutionally, the SCBR principle serves as an instrument for fulfilling the right to access to justice, ideally aligning with the Islamic legal maxims of taysīr (facilitation) and rafʿ al ḥaraj (removal of hardship) within maqāṣid al sharīʿah. Employing a normative legal method with a doctrinal analytical design, this research synthesizes procedural justice theory, utilitarianism, and Islamic legal philosophy to comprehensively examine the alignment between legal norms and judicial practice. The analysis reveals a philosophical tension between formal legal certainty and substantive justice, wherein complex procedures disproportionately marginalize petitioners from economically disadvantaged backgrounds. Furthermore, digital transformation through the e-Court system has yet to address the restructuring of substantive case examinations, meaning that administrative efficiency does not automatically guarantee substantive justice. The study concludes that the SCBR principle must be constructed as a binding judicial interpretive guideline rather than merely an administrative directive. Strategic recommendations include the application of teleological interpretation, cost standardization based on petitioners' economic capacity, and the simplification of evidentiary procedures. This research bridges the dichotomy between legal formalism and substantive justice, while simultaneously offering a philosophical foundation for a more inclusive and socially responsive reform of the Religious Courts. These findings are expected to serve as a policy reference for the Supreme Court in drafting technical guidelines for isbat cerai that prioritize substantive justice.